Regionalne inwestycje publiczne w Polsce w latach 2008–2013 - Jarosiński, Krzysztof (Kwartalnik Kolegium Ekonomiczno-Społecznego. Studia i Prace, 2015)
The main objective of the Polish investment policy during transition and accession to the European Union was to increase investment in both the private and the public sector. The investment policy at that time had to be conducted on the basis of far-reaching autonomy of public sector units. The article concentrates on the economic analysis and evaluation of the effects of regional investment policy, focusing on the expenditures between 2008–2013.